Determination of Points on the Surfaces - Juraeva Khusnora Davronovna; Yuldashev Akmal Olimovich (Genius Journals, 2022)
In order to determine the position of a point on the surface, the height of the points is determined as a result of leveling. First of all, you need to know the initial mark. During the observations, a zero point was obtained in relation to the dry part of the sea level, i.e., the shores, in order to know the point state of the earth's surface. The distance from the level surface passing through the point to the level surface, which is assumed to be the beginning of the count, is the altitude. Determining the position of a point on the surface, that is, measuring it above sea level, takes a long time. Each state has its own zero point and accepts a certain sea level.
Keywords: International altitude systems; absolute; relative